Self-sampling and self-testing for HIV at a commercial and community-based test provider in the Netherlands: user preferences and usability - I. J. M. Willemstein; O. Shobowale; A. M. Żakowicz; H. Bos; E. L. M. Op de Coul (BMC Health Services Research)
Abstract HIV self-sampling and -testing (HIVSS/ST) reduces testing barriers and potentially reaches populations who may not test otherwise. In the Netherlands, at-home HIV tests became commercially available around 2016, but data on user experiences are limited. This study aimed to explore characteristics of users and their experiences with HIVSS/ST. In 2022 and 2023, a survey was distributed among users of one online commercial provider and one community-based provider; either users ordered a commercial online HIVSS/ST or they sought a free-of-charge HIVST via the community-based provider. Questions included usability, preferences, and barriers of HIVSS/ST-testing. We compared characteristics and experiences of users between providers, risk groups and first-time and repeat testers. In total, 133 users completed the survey; 89 (67%) via the commercial provider and 44 (33%) via the community-based provider. Response rates per provider were 2% and 26%, respectively. Users who bought their test at the commercial provider were more often Gay and Bisexual Men (GBM) (42%), 35 + years (43%), and born in the Netherlands (89%), compared to those recruited through the community-provider (respectively 27%, 25%, 14%). GBM were more often repeat and recent HIVSS/ST-testers, and using pre-exposure prophylaxis (PrEP). Women and heterosexual men were more likely to buy an HIVSS/ST as part of a combination Sexually Transmitted Infections (STI) test package. Overall, main reasons for choosing HIVSS/ST were saving time (42%), anonymity (36%) and not having to talk to a GP (35%). Twenty-two percent of the study participants experienced some problems performing the HIVSS/ST, the most reported problem was obtaining sufficient blood through the finger prick (71%). Recommendations to improve accessibility of HIVSS/ST included more awareness (advertising by trustful providers), more access locations (pharmacies/supermarkets/schools) and lower costs. Our findings indicate that HIVSS/ST is a valuable additional HIV testing method for users, but more insight into the contribution of HIVSS/ST to HIV prevention policies is needed.